The need for primary quality control of commercially available immunoassay kits. Issue 2 (February 1991) - Hashimoto, T; Matsubara, F
Abstract : Discrepancies among three commercially available luteinising hormone (LH) radioimmunoassay RIA kits, all calibrated against the second-IRP-HMG (World Health Organisation International Laboratory for Biological Standards), were observed. Even though the Japan Radioisotope Association carries out external quality control in Japan every year, inaccuracies still exist. This problem also exists elsewhere, and it is proposed that a global monitoring system of primary quality control (PQC) should be introduced by a body such as the World Health Organisation.